Genomic profiling of NETs: a comprehensive analysis of the RADIANT trials. Issue 4 (April 2019) - Yao, James; Garg, Abhishek; Chen, David; Capdevila, Jaume; Engstrom, Paul; Pommier, Rodney; Van Cutsem, Eric; Singh, Simron; Fazio, Nicola; He, Wei; Riester, Markus; Patel, Parul; et al.
Abstract : Neuroendocrine tumors (NETs) have historically been subcategorized according to histologic features and the site of anatomic origin. Here, we characterize the genomic alterations in patients enrolled in three phase 3 clinical trials of NET of different anatomic origins and assess the potential correlation with clinical outcomes. Whole-exome and targeted panel sequencing was used to characterize 225 NET samples collected in the RADIANT series of clinical trials. Genomic profiling of NET was analyzed along with nongenomic biomarker data on the tumor grade and circulating chromogranin A (CgA) and neuron-specific enolase (NSE) levels from these patients enrolled in clinical trials. Our results highlight recurrent large-scale chromosomal alterations as a common theme among NET. Although the specific pattern of chromosomal alterations differed between tumor subtypes, the evidence for generalized chromosomal instability (CIN) was observed across all primary sites of NET. In pancreatic NET, although the P value was not significant, higher CIN suggests a trend toward longer survival (HR, 0.55, P  = 0.077), whereas in the gastrointestinal NET, lower CIN was associated with longer survival (HR, 0.44, P  = 0.0006). Our multivariate analyses demonstrated that when combined with other clinical data among patients with progressive advanced NETs, chromosomal level alteration adds important prognostic information. Large-scale CIN is a common feature of NET, and specific patterns of chromosomal gain and loss appeared to have independent prognostic value in NET subtypes. However, whether CIN in general has clinical significance in NET requires validation in larger patient cohort and warrants further mechanistic studies.